Causes of cancer - Bozzone, Donna M. (Biology cancer, 2007)
Examines the biology of cancer, focusing on the causes of cancer, looking at infectious agents, radiation, and occupational and environmental carcinogens, and considering whether the disease can be inherited or prevented. . Includes a glossary and resources for further research